Analysis of Leptospirosis Incidence Based on Occupation and Knowledge in the Work Area of the Tulakan Community Health Center, Pacitan Regency in 2025 - Trianto, Agung; Hargono, Arief; Arini, Ratih Dwi (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2026)
Introduction: Leptospirosis is a zoonotic disease caused by the bacteria Leptospira interrogans and which is transmitted from animals to humans through direct contact with the urine of infected animals or contaminated environments, the main transmitting animals are rats. This study aimed to analyze the risk factors of sex, age, occupation, and knowledge and whether they influenced the incidence of leptospirosis. in the working area of the Tulakan Community Health Center, Pacitan Regency in 2025.Method: This type of research is a quantitative analytical research with a cross-sectional design. The sample in this study comprised the entire population of 152 participannt. Data were collected using secondary data observation techniques, leptospirosis case data, and primary data, including sex, age, occupation, and knowledge. Further data analysis was performed using univariate (frequency distribution) and bivariate (chi-square test) analyses.Results: The results of the bivariate analysis show only occupation variables is associated with the incidence of leptospirosis (P-value= 0.000 PR= 15.054; 95% CI= 5.763-39.323) and also the knowledge variable is statistically significant with the incidence of leptospirosis (P-value= 0.005 PR= 3.689; 95% CI= 1.432-9.504). Age and sex did not significantly influence the incidence of leptospirosis.Conclusion: Occupation and knowledge significantly influenced the incidence of leptospirosis in the area served by the Tulakan Community Health Center, Pacitan Regency in 2025.